Giants & witches, and a dragon or two - Fenner, Phyllis Reid 1899-; Pitz, Henry Clarence 1895-1976. (New York Knopf, 1943)
Seventeen stories, including both folk tales and a few original stories, about various creatures of fantasy, including Baba Yaga, King Stork, Jack the Giant Killer, and The Terrible Olli.
Keywords: Children's stories; Folklore; Fairy tales